2008
DOI: 10.1007/s00264-008-0697-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological results of arthroscopically treated tibial spine fractures in childhood

Abstract: The objective of this study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 22 publications
2
72
1
Order By: Relevance
“…One study demonstrated that tibial eminence fractures were more likely to occur rather than ACL tears when loading rates were slower [5,6]. This study also noted some plastic deformation with permanent elongation of ACL fibers prior to the fracture occurring, which may cause the clinical laxity that can accompany these injuries despite anatomic fracture reduction [11][12][13].…”
Section: Mechanism Of Injury/symptomsmentioning
confidence: 82%
“…One study demonstrated that tibial eminence fractures were more likely to occur rather than ACL tears when loading rates were slower [5,6]. This study also noted some plastic deformation with permanent elongation of ACL fibers prior to the fracture occurring, which may cause the clinical laxity that can accompany these injuries despite anatomic fracture reduction [11][12][13].…”
Section: Mechanism Of Injury/symptomsmentioning
confidence: 82%
“…Also, it has been noted with these fractures there is variable degree of plastic deformation with permanent elongation of ACL fibers which may cause residual clinical laxity despite anatomic reduction and healing of fracture [10-12]…”
Section: Biomechanics Of Pediatric Acl Injurymentioning
confidence: 99%
“…34,39,43,44 However, recently many authors report minimal incidence of arthrofibrosis after arthroscopic rigid fixation and early mobilization within 2 to 4 weeks, indicating that early mobilization can reduce the rate of arthrofibrosis and improve the outcome. [15][16][17][18]41 In our study, only two patients (7.7%) had postoperative knee stiffness who recovered completely after arthroscopic adhesiolysis. One patient, who was 12-year-old, had 10-degree extension deficit.…”
Section: Complicationsmentioning
confidence: 97%